Visual inspection with acetic acid and cytology in the early detection of cervical neoplasia in Kolkata, India. Issue 5 (1st August 2003) - Basu, P. S.; Sankaranarayanan, R.; Mandal, R.; Roy, C.; Das, P.; Choudhury, D.; Bhattacharya, D.; Chatterjee, R.; Dutta, K.; Barik, S.; Tsu, V.; Chakrabarti, R. N.; et al.
Abstract : Visual inspection of the cervix after application of 3–5% acetic acid (VIA) is a potential alternative to cytology for screening in low-resource countries. The present study evaluated the performance of VIA, magnified visual inspection after application of acetic acid (VIAM), and cytology in the detection of high-grade cervical cancer precursor lesions in Kolkata (Calcutta) and suburbs in eastern India. Trained health workers with college education concurrently screened 5881 women aged 30–64 years with VIA, VIAM, and conventional cervical cytology. Detection of well-defined, opaque acetowhite lesions close to the squamocolumnar junction; well-defined, circumorificial acetowhite lesions; or dense acetowhitening of ulceroproliferative growth on the cervix constituted a positive VIA or VIAM. Cytology was considered positive if reported as mild dysplasia or worse lesions. All screened women ( N = 5881) were evaluated by colposcopy, and biopsies were directed in those with colposcopic abnormalities ( N = 1052, 17.9%). The final diagnosis was based on histology (if biopsies had been taken) or colposcopic findings, which allowed direct estimation of sensitivity, specificity, and predictive values. Moderate or severe dysplasia or carcinoma in situ (CIN 2–3 disease) was considered as true positive disease for the calculation of sensitivity, specificity, and predictive values of screening tests. 18.7%, 17.7% and 8.2% of the women tested positive for VIA, VIAM, and cytology. One hundred twenty two women had a final diagnosis of CIN 2–3 lesions. The sensitivities of VIA and VIAM to detect CIN 2–3 lesions were 55.7% and 60.7%, respectively; the specificities were 82.1% and 83.2%, respectively. The sensitivity and specificity of cytology were 29.5% and 92.3%, respectively. All the tests were associated with negative predictive values above 98%. VIA and VIAM had significantly higher sensitivity than cytology in our study; the specificity of cytology was higher than that of VIA and VIAM.